Literature Reviews for Education and Nursing Graduate Students - Frederiksen, Linda; Phelps, Sue F. (Open textbook library., 2017)
Literature Reviews for Education and Nursing Graduate Students is an open textbook designed for students in graduate-level nursing and education programs. Its intent is to recognize the significant role the literature review plays in the research process and to prepare students for the work that goes into writing one. Developed for new graduate students and novice researchers just entering into the work of a chosen discipline, each of the eight chapters covers a component of the literature review process. Students will learn how to form a research question, search existing literature, synthesize results and write the review. The book contains examples, checklists, supplementary materials, and additional resources. Literature Reviews for Education and Nursing Graduate Students is written by two librarians with expertise guiding students through research and writing assignments, and is openly licensed.